Perwujudan Etika Islam dalam Bermedia Sosial melalui Karya Jurnal Ilmiah Siswa sebagai Implementasi Kurikulum Merdeka di SMA Al Islam 1 Surakarta - Galih Pranata; Wiwit Maharesti; Anjar Miska Prayoga; Anggitya Alfiansari (UIN Imam Bonjol Padang, 2022)
Students at SMA Al Islam 1 Surakarta actually have sensitivity to the surrounding environment, not least in seeing and critically assessing the behavior of their peers in social media. It's just that students' concerns about Islamic ethics in social media need to be poured into positive things, such as writing a journal. This study aims to examine students' understanding of Islamic ethics and the challenges they face in writing scientific journals. The results of this study indicate the existence of an independent curriculum as a facilitator to encourage students to write scientific journals.